Analysis of uranium mobility and concentration process in objects of environment and patients’ kidney stones in Kharkiv region - Dikiy, N.P.; Lisovoy, V.N.; Bereznyak, E.P.; Kolupayev, S.M.; Lyashko, Yu.V.; Medvedeva, E.P.; Medvedev, D.V.; Hodyreva, Y.S. (Вопросы атомной науки и техники, 2021)
The specific activity of ²³⁵U and content of native uranium for the Kharkiv region in drinking water, soil, roots, the leaf of hydrophyte “Pistia stratiotes” and the samples of kidney stones obtained from patients with urolithiasis were measuring by using gamma activation analysis on linac accelerator of NSC KIPT. The whole sample contained alpha-emitter uranium.